Scandium catalysed stereoselective thio-allylation of allenyl-imidates. Issue 65 (25th July 2019) - Parodi, Adriano; Battaglioli, Simone; Liu, Yang; Monari, Magda; Marín-Luna, Marta; Silva-López, Carlos; Bandini, Marco
Abstract : The site-selective thio-allylation of electron-deficient 1, 2-dienes is documented under scandium catalysis. Abstract : The site-selective thio-allylation of electron-deficient 1, 2-dienes is documented under scandium catalysis. The methodology enables the realization of α-β unsaturated, β-thio, γ-allyl carboxylic acid derivatives via a one-pot Lewis acid promoted Michael addition/[3, 3]-sigmatropic rearrangement sequence (20 examples) in high yields (up to 95%). Full rationalization of the reaction mechanism and stereochemical outcome is provided via DFT simulations.